Harvesting water surface energy: self-jumping nanostructured hydrophobic metals - Jing Yuan Tsai; Guan Fu Huang; Jiann Shieh; Chin Chi Hsu; Kostya (Ken) Ostrikov (iScience, 2021)
Summary: Water in motion is a significant energy source worldwide, but the surface energy of water is rarely utilized as a power source. In this study, we made metals unsinkable and able to jump out of the water by harvesting the water surface energy. This effect is attributed to the enhanced floating ability of the nanostructures on copper and stainless steel foil surfaces. Sufficiently thin hydrophobic metals can slowly float underwater through air trapping at the surface and then rapidly leap out of the water on contact with the water-air interface. The mechanism is related to the surface energy of the water, which contributes to the 15 mg metals with a power of 0.49 μW experiencing rapid changes in velocity and acceleration at the interface. The conversion of surface energy to eject nanostructured hydrophobic materials from the liquid surface may lead to new solid-liquid separation techniques.